Effect of Off-pump Coronary Artery Bypass Graft Surgery in Patients with Diabetes Mellitus (Ibrahim Cardiac Medical Journal, 2019)
Background & objective : Myocardial revascularization in diabetic patients is challenging. Off pump coronary artery bypass (OPCAB) surgery has been widely used for the treatment of coronary artery disease. The goal of this study was to compare outcomes of OPCAB in diabetic patients relative to non diabetic patients.Methods:The present prospective study was conducted between January 2014 to June 2017. During the period a total of 193 patients (of whom 70 had diabetes and 123 patients were non-diabetics) were included in the study. All of them underwent coronary artery bypass grafting (CABG) without cardiopulmonary bypass surgery. The early clinical outcomes of OPCAB were evaluated during the postoperative hospital stay.Result: Over three-quarters of the patients in both diabetic and non-diabetic groups were ≥ 50 years old with no significant intergroup difference (p = 0.825). Majority(90%) of the patients in either group was male (p = 0.786). Nearly half (48.5%) of the patients in diabetic and 45% in non-diabetic group were overweight or obese (p = 0.557). The smokers weremuch higher in non-diabetic group than that in the diabetics (p = 0.009). The average number of grafts needed was considerably higher in the diabetic group (p = 0.079). All the postoperative outcome variables like pneumonia, stroke, arrhythmia, renal failure requiring dialysis and postoperative mortality in both the groups were almost identical (p > 0.05).Conclusion: Off-pump coronary artery bypassis the preferred choice of revascularization for multi-vessel coronary artery disease in diabetic patients. However, continuous, strict glycemic control is essential to have a good postoperative outcome.Ibrahim Card Med J 2018; 8 (1&2): 10-16